Measuring the impact of a mandatory province-wide vaccinate-or-mask policy on healthcare worker absenteeism in British Columbia, Canada. Issue 30 (9th July 2019) - Murti, Michelle; Otterstatter, Michael; Orth, Alison; Balshaw, Robert; Halani, Khalif; Brown, Paul D; Hejazi, Samar; Thompson, Darby; Allison, Sandra; Bharmal, Aamir; Dawar, Meena; Hoyano, Dee; et al.
Highlights: In 2012, British Columbia introduced a vaccinate-or-mask policy for HCWs. We assessed HCW all-cause sick time before and after policy implementation. Overall sick rates increased post-policy in both influenza and non-influenza seasons. We found opposite trends in influenza and non-influenza season sick time usage patterns. Changes in sick time patterns need further evaluation to understand potential policy impacts. Abstract: Objectives: Vaccinate-or-mask (VOM) policies aim to improve influenza vaccine coverage among healthcare workers (HCW) and reduce influenza-related illness among patients and staff. In 2012, British Columbia (BC) implemented a province-wide VOM influenza prevention policy. This study describes an evaluation of policy impacts on HCW absenteeism rates from before to after policy implementation. Methods: Using payroll data from regional and provincial Health Authorities (HA), we assessed all-cause sick rates (sick time as a proportion of sick time and productive time) before (2007–2011, excluding 2009–2010) and after (2012–2017) policy implementation, and during influenza season (December 1–March 31) and non-influenza season (April 1–November 30). We used a two-part negative binomial hurdle model to calculate odds ratios (OR) of taking any sick time, relative rates (RR) of sick time taken, and predicted mean sick rates, adjusting for age group, sex, job type, job classification, HA, year and vaccine effectiveness. Results: During influenza season, HCWs in the post-policy period were less likely to take any sick time (OR 0.989, 95%CI: 0.979–0.999) but had higher rates of sick time (RR 1.038, 95%CI: 1.030–1.045). However, during non-influenza season, HCWs in the post-policy period were more likely to take any sick time (OR 1.015, 95%CI: 1.008–1.022) but had lower rates of sick time (RR 0.971, 95%CI: 0.966–0.976). There was an overall increase in predicted mean sick rate from pre to post-policy in influenza season (4.392% to 4.508%) and non-influenza season (3.815% to 3.901%). Conclusions: The observed year-round increase in sick rates from pre-to-post policy was likely influenced by other factors; however, opposite trends in how HCWs took sick time in the influenza and non-influenza seasons may reflect policy influences and need further research to explore reasons for these differences.